Reliability of shoulder muscle endurance tested using elastic bands - Micheletti, Jéssica K. [UNESP]; Andersen, Lars L.; Machado, Aryane F. [UNESP]; Lopes, Jaqueline S.; Souto, Larissa R. [UNESP]; Pastre, Carlos M. [UNESP] (Edizioni Minerva Medica, 2019)
BACKGROUND: Elastic bands are commonly used as resistance training device in clinical settings and at workplaces due to its easy handling, low cost and safety. Studies have supported this tool as evaluation of muscular strength; however, no standardized methods for testing localized muscular endurance exist. The purpose is to evaluate reliability of performance during a newly developed shoulder abduction endurance test with elastic bands. METHODS: A total of 28 healthy adults participated in 4 sessions: Orientation, Familiarization, Test, and Retest. For muscle endurance testing participant performed repeated shoulder abductions to 90ºuntil fatigue at two levels of elastic bands above 50% of the 1RM (average of 76.1±3.5% from 1RM). The reliability analyses were performed using the intraclass correlation coefficient (ICC) with 95% confidence interval and typical measurement error (TME), present also in coefficient of variation (CV%) for total time to fatigue, repetition, and total work. RESULTS: For test and retest, respectively, time to fatigue was 65.9±13.6 and 66.0±15.0 seconds (P=0.96), repetition 22.1±4.5 and 22.2±5.3 (P=0.86). The variables showed satisfactory reliability (time: ICC=0.83 [95% CI=0.67; 0.92]; repetition: ICC=0.78 [95% CI=0.57; 0.89]; total work: ICC=0.89 [95% CI=0.63; 0.97]). CONCLUSIONS: The test for shoulder muscle endurance using elastic resistance bands has good reliability, and can therefore be recommended in settings where muscle endurance is of importance.
Keywords: Fatigue; Reproducibility of results; Resistance training